Recueil de decisions (9e edition). (International Monetary Fund, 1978)
This paper presents Selected Decisions and Selected Documents' Supplement to Eighth issue of the IMF. This volume, which is presented as a Supplement to the Eighth Issue of Selected Decisions of the IMF and Selected Documents includes general decisions adopted by the IMF since May 10, 1976, the date of publication of the Eighth Issue. Some of these decisions were adopted in connection with the Second Amendment of the IMF's Articles of Agreement that took effect on April 1, 1978. All references to the Articles and to the By-Laws, Rules and Regulations in this Supplement are to the Articles of Agreement as modified by the Second Amendment and to the By-Laws, Rules and Regulations of the Thirty-Fifth Issue, July 1, 1978, respectively, unless indicated otherwise. The IMF has not yet completed the process of making the modifications in existing decisions, and adopting the new decisions, that are required in connection with the Second Amendment. The Ninth Issue of this collection will be published as soon as this task of adaptation is complete. It will include the decisions in the Eighth Issue that remain in effect, the decisions in this Supplement, and any further decisions that are adopted. Meanwhile, in view of the accumulation of new and modified decisions, there is need for this Supplement.